Lingual Lipase and Its Role in the Digestion of Dietary Lipid - Hamosh, Margit (1973)
The serous glands of rat tongue were found to contain a potent lipolytic enzyme which hydrolyzed triglyceride to mostly diglyceride and free fatty acids (FFA) at pH 4.5-5.4. Homogenates of lingual serous glands from adult rats hydrolyzed 40-70 mmol of triglyceride/g per h. The soft palate, anterior oral pharyngeal wall, and lateral oral pharyngeal glands also contained the activity, but at a much lower level. The lipolytic activity was also found in saliva collected through an esophageal cannula and in stomach contents of rats fed a fat-rich meal. The stomach contained very little activity, however, when saliva was excluded. Lipolytic activity was not found in the stomach wall or in the parotid, submandibular, and sublingual glands. The findings suggest that the lingual serous glands secrete a lipase which catalyzes in the stomach the conversion of triglyceride to partial glycerides and FFA. It is proposed that this reaction is the first step in the digestion of dietary lipid.